Anterior chamber angle granuloma: A rare ocular manifestation of histoid lepromatous leprosy - Deepak Soni; Bhavana Sharma; Samendra Karkhur (Indian Journal of Ophthalmology, 2020)
Leprosy is a chronic multisystem disease caused by Mycobacterium leprae with frequent ocular manifestations such as madarosis, lagophthalmos, lid abnormalities, impaired corneal sensations, chronic uveitis, and cataract. Granulomas are characteristic lesion of lepromatous leprosy commonly seen as conjunctival and iris granulomas. We report a case of leprosy with a rare ocular manifestation in the form of angle mass lesion or suspected granuloma which has not been reported before and its successful management following treatment with favorable outcome. The index case also highlights the anterior segment fluorescein angiography features of the lesion and study of its vascular pattern.